PENGARUH ATRIBUT PRODUK COFFEE SHOPS TERHADAP KEPUASAN DAN LOYALITAS (Studi pada pengunjung wanita) - Kurniawan, Ardi; Riza Firdaus, Muhammad (JWM (JURNAL WAWASAN MANAJEMEN), 2024)
The sample is 200 female customers of coffee shops in the medium - high category that carry the contemporary and instagramable concept. Data analysis using SEM-PLS. Results was shown that product attributes have an effect on female customer satisfaction. Product attributes are related atmosphere, employee attitude/service, IT Services, coffee quality, variant menu, and product price. Furthermore, customer satisfaction has an effect on female customer loyalty.